Reinforcement of plastic using empty fruit bunch (EFB) of palm oil waste - Shahrul Anuar, Abd Rahman (2010)
The use of natural fiber as a reinforcement in polymer composites are getting so much attention and widely used for technical application in automotive , furniture, aerospace ,packaging and others industries. demand and attraction for alternatively material from renewable resource are incredibly increased. Awareness the come out from precision analysis in many aspects for example safety, environmental impact, health and cost saving for composites production had produce one new idea in finding an alternative way to replace the limited resource material like synthetic material. The environmental issue and lower cost for natural fiber and lignocelluloses resource had attract many researcher in the entire world to make this materials as a reinforce material in composite engineering. The main resource is get from agriculture sector that produce as a waste like grain husk, pineapple leaves, kenaf, jut and coir. The objective of this research is to determine the effect of alkaline treatment on this fiber, to produce high quality fiber by treatment process and to find the effect of natural fiber reinforcement with epoxy (plastic).Method that was used in making these plastic reinforcement composites are thermosetting process where the liquefy epoxy resin will be combine with empty fruit bunch (EFB) of oil palm fiber with hot press equipment. The empty fruit bunch fiber will be treat first with alkaline treatment to remove the lignin contain and increase the surface roughness. Alkali treatment also can make fiber more hydrophobic in order to get good interfacial adhesion between fiber and thermoset polymer matrix. The resulted are 10% treatment with NaOH give the best result from effective and economic side where provide tensile strength of 14.9 MPa for 10% fiber loading where it can be used for structural applications.